2020
DOI: 10.7150/thno.46568
|View full text |Cite
|
Sign up to set email alerts
|

Nanozyme-assisted sensitive profiling of exosomal proteins for rapid cancer diagnosis

Abstract: The proteins expressed on exosomes have emerged as promising liquid-biopsy biomarkers for cancer diagnosis. However, molecular profiling of exosomal proteins remains technically challenging. Herein, we report a nanozyme-assisted immunosorbent assay (NAISA) that enables sensitive and rapid multiplex profiling of exosomal proteins. This NAISA system is based on the installation of peroxidase-like nanozymes onto the phospholipid membranes of exosomes, thus avoiding the need for post-labelling detection antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 48 publications
(46 reference statements)
3
43
0
Order By: Relevance
“…Altogether, PD-L1 appears to be a helpful diagnostic biomarker for indeterminate nodules, whether at the mRNA or protein level and in tissues or serum 48 , 50 , 52 , 54 , 57 . Nevertheless, no study has been designed specifically for this subgroup of patients.…”
Section: The Pd-1/pd-l1 Axis In Thyroid Diseasesmentioning
confidence: 96%
See 4 more Smart Citations
“…Altogether, PD-L1 appears to be a helpful diagnostic biomarker for indeterminate nodules, whether at the mRNA or protein level and in tissues or serum 48 , 50 , 52 , 54 , 57 . Nevertheless, no study has been designed specifically for this subgroup of patients.…”
Section: The Pd-1/pd-l1 Axis In Thyroid Diseasesmentioning
confidence: 96%
“…Consistent with its prognostic value in other malignancies 56 , Aghajani et al . showed that a high level of soluble PD-L1 in serum, over 0.44 ng/ml, and its detection in matched tumor tissues were associated with a significantly shorter PFS in PTC patients (uni- and multivariate analyses) 57 . As a result, this study places PD-L1 in serum as a marker of bad prognosis for WDTC 57 .…”
Section: The Pd-1/pd-l1 Axis In Thyroid Diseasesmentioning
confidence: 97%
See 3 more Smart Citations